Incorporating the Study of Knowledge into the IPE Mainstream, or, When Does a Trade Agreement Stop Being a Trade Agreement? - Haggart, Blayne (Journal of information policy (University Park, Pa.), 2017)
The treatment of knowledge—most notably commodified knowledge—as a source and vector of power potentially is a key blind spot in our understanding of the global political economy. This article offers a theoretical framework, based on the work of Susan Strange, for considering the relationship between what she called the “knowledge structure” and the other key sources of political and economic power—security, production, and finance. This framework is applied to the Trans-Pacific Partnership, demonstrating how a direct focus on knowledge governance reveals power relations and economic effects that are otherwise obscured.